The Effect of Expungement on Removability of Non-Citizens - Nafziger, James A.R. (2003)
For most of the twentieth century, a non-citizen was generally not subject to removal on the basis of a criminal conviction which had been expunged by the state that rendered the conviction. During that time, the definition of a conviction for purposes of immigration law was borrowed from the law of the state which rendered the criminal conviction. In the Illegal Immigration Reform and Immigrant Responsibility Act (IRIRA) of 1996 Congress sought to provide a more uniform definition of the term conviction sufficient to justify an order of removal under the immigration law. The IIRIRA does not mention expungement, however. This Article argues that the Board of Immigration Appeals (BIA) and courts have misconstrued the IIRIRA. In 1999 the BIA first dealt with the effect of a state expungement under the statute. This Article argues that the BIA's decision in Matter of Roldan improperly reversed more than a half-century of precedent by refusing to give effect to a state expungement of a non-citizen's conviction unless expressly provided by federal statute. Judicial decisions have since accepted this rule. Part I of this Article reviews state expungement statutes. Part II summarizes cases prior to the IIRIRA. Part III explains the IIRIRA and Matter of Roldan. Part IV addresses recent cases concerning the effect of a state expungement on removability, arguing that these cases have either misconstrued the IIRIRA or improperly applied the Chevron doctrine. Part V compares the current state of the law with immigration laws abroad, arguing that the exceptional result reached by United States courts is further evidence that Matter of Roldan and its progeny are mistaken